Fraud detection in the procurement of goods and services - Ramadhan, Muh. Syahru; Adhim, Chairul (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2021)
This study aims to determine the various factors that can affect the detection of fraud in the procurement of goods and services. Sampling with a certain sampling method. The research data were tested using multiple regression test. This study found that the competence of human resources has a negative and significant effect on fraud detection. Meanwhile, facilities and infrastructure, internal control systems, and quality audit probity all have a positive and significant effect on fraud detection. However, the pressure on the time budget does not affect the detection of fraud. Auditors have proven to have the experience and competence to carry out their duties. In addition, the available facilities and infrastructure as well as the structure of the Internal Audit unit as well as the quality of the probability audit are in accordance with the needs. The results of the study can be used as a reference for evaluating the performance of audit probity to detect fraud and improve the management system for the procurement of goods and services in the Dompu government. Quantitative research to detect fraud in the procurement of goods and services is still very limited, and this research is the first where the sample is from the party conducting the probity audit (Inspectorate), the planning party (DPPKAD/Department of Revenue, Financial Management and Regional Assets), and implementation (ULP/Procurement Service Unit) acquisition of goods and services.